True wellness the mind : how to combine the best of Western and Eastern medicine for opimal health; sleep disorders anxiety, depression - Kurosu, Catherine (True wellness., 2019)
A step-by-step guide to optimal mental health, blending the best of Western and Eastern medical traditions to address sleep disorders, anxiety, and depression. The authors explain how exercise, nutritious food, stress management, acupuncture, and qigong affect the body, so you can make healthier choices. To help you move forward on a new path, they provide practical advice and worksheets to start simple daily exercise routines, eat a plant-based diet, and begin qigong practice.--Publisher.